A new approach to the reactive current detection in three-phase systems under nonsinusoidal voltage condition - Xiaobin Zhang; Yanru Zhong (2011 6th IEEE Conference on Industrial Electronics and Applications, 2011)
According to the defect of the instantaneous reactive power theory under nonsinusoidal voltage condition, the rotating frame detection algorithm is proposed. The reactive current can be detected accurately under nonsinusoidal voltage condition by the detection algorithm. Compared with other rotating frame detection algorithms, the algorithm only need the voltage and current instantaneous values instead of the voltage phase angle. This effectively simplifies the hardware detection circuit.